2022
DOI: 10.1155/2022/7530102
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Mediated miR-21 Was Involved in the Promotion of Structural and Functional Recovery Effect Produced by Electroacupuncture in Sciatic Nerve Injury

Abstract: Purpose. Our study is aimed at investigating the mechanism by which electroacupuncture (EA) promoted nerve regeneration by regulating the release of exosomes and exosome-mediated miRNA-21 (miR-21) transmission. Furthermore, the effects of Schwann cells- (SC-) derived exosomes on the overexpression of miR-21 for the treatment of PNI were investigated. Methods. A sciatic nerve injury model of rat was constructed, and the expression of miR-21 in serum exosomes and damaged local nerves was detected using RT-qPCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 119 publications
(107 reference statements)
2
13
0
Order By: Relevance
“…Moreover, the inhibition of exosomal miR-21 eliminated the protective effects of neurons via the AKT pathway ( Gao et al., 2020 ). Our previous results also showed that SC-derived exosomal miR-21 promoted neurite outgrowth in vitro ( Liu et al., 2022a , 2022b ), while upregulation of miR-21 in MSCs-derived exosomes can also inhibit neuronal apoptosis ( Xu et al., 2019 ). Together with results from in vivo studies ( Wang et al., 2020a ), we believe that SC-derived exosomal miR-21 is involved in the pathogenesis of DPN and may be a promising target for DPN treatment.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Moreover, the inhibition of exosomal miR-21 eliminated the protective effects of neurons via the AKT pathway ( Gao et al., 2020 ). Our previous results also showed that SC-derived exosomal miR-21 promoted neurite outgrowth in vitro ( Liu et al., 2022a , 2022b ), while upregulation of miR-21 in MSCs-derived exosomes can also inhibit neuronal apoptosis ( Xu et al., 2019 ). Together with results from in vivo studies ( Wang et al., 2020a ), we believe that SC-derived exosomal miR-21 is involved in the pathogenesis of DPN and may be a promising target for DPN treatment.…”
Section: Discussionmentioning
confidence: 67%
“…Multiple miRNAs were down- and upregulated in diabetes, and have been shown not only to play an important role in the pathogenesis of T2D ( Moura et al., 2014 ; Ozdemir and Feinberg, 2019 ) but also to be potential biomarkers for the development and progression of T2D as estimated by their circulating levels ( Dehwah et al., 2012 ). Recent studies have reported that miR-21 is involved in regulating T2D glucose metabolism by promoting insulin secretion, further revealing the potential mechanism of miR-21 in regulating the pathogenesis of DPN ( Liu et al., 2022a , 2022b ). As a widely studied miRNA molecule, miR-21 was found to be closely related to peripheral neuropathy ( Karl et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the hsa-miR-200c-3p, related to PTPRD and TBK1 ( Table 3 and Figure 3 ), was found to be a key factor that promotes successful spinal cord regeneration in axolotls, regulating the stem cell identity [ 123 ]. The hsa-miR-21-5p, related to KIFAP3, was recently shown to be involved in the promotion of structural and functional recovery in sciatic nerve injury [ 124 ]. The hsa-miR-222-3p, related to COG2, KIF5C, and KIF3B ( Supplementary Table S1 , Table 3 , and Figure 3 ) enhanced the neuronal differentiation of neural stem cells and thus the combination of nanofibrous scaffolds with miR-222 is proposed as a promising approach for neural tissue regeneration [ 125 ].…”
Section: Do the Same Non-coding Rnas Control Neuroregeneration And Al...mentioning
confidence: 99%
“…It has been reported that exosomal miR-34c-5p regulates ICC in STC model rats by targeting SCF. Besides, electroacupuncture (EA) can regulate exosomes, exosomal miRNAs, and exosomal circRNAs [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%